Photochemical synthesis of nanosheet tin di/sulfide with sunlight response on water pollutant degradation - Matmin J.; Jalani M.A.; Osman H.; Omar Q.; Ab'lah N.; Elong K.; Kasim M.F. (MDPI AG, 2024)
Indexed by Scopus